A retrospective analysis of the utility of myocardial perfusion imaging using single photon emission computed tomography (SPECT) for differentiating ischaemic from non-ischaemic left ventricular dysfunction - Singh, Alosha (My University, 2017)
Differentiating ischaemic left ventricular dysfunction (ILVD) from non-ischaemic left ventricular dysfunction (NILVD) is crucial since appropriately selected patients may benefit from coronary revascularisation. The aim of this study was to evaluate the diagnostic utility of myocardial perfusion imaging (MPI) in patients presenting with left ventricular dysfunction using coronary angiography (CA) as the gold standard. Methods This single centre retrospective study was conducted in 52 patients with heart failure with a reduced ejection fraction (EF< 40%) who had both MPI as well as CA at CHBAH between January 2005 and December 2012. ILVD was diagnosed when the distribution and severity of coronary disease on CA was sufficient to account for the degree of left ventricular dysfunction. Results From a total of 52 patients, 33 (63%) had ILVD and 19 (37%) had NILVD. As compared to patients with NILVD, those with ILVD were more likely to be Indian and White (p=0.0014), have more coronary risk factors (5(2) vs 3(2), p < 0.0001) and more commonly have q waves on the ECG (0% vs 55%, p < 0.0001). MPI had a sensitivity of 100% (95% CI 66-100%) and specificity of 52.63% (95% CI 30.18 - 75.08) for the diagnosis of ILVD. The presence of fixed perfusion defects on MPI was the best predictor of ILVD. Conclusion MPI has high sensitivity but low specificity for the diagnosis of ILVD. This makes it a useful screening test for the exclusion of coronary artery disease in patients presenting with heart failure.
A research report submitted to the Faculty of Health Sciences in fulfilment of the requirements for the degree of Master of Medicine, in Internal Medicine at the University of Witwatersrand, Johannesburg. September 2017
Keywords: Myocardial Perfusion Imaging; Tomography, Emission-Computed, Single-Photon (SPECT)